Investigasi Empiris Upaya Meningkatkan Employee Performace Dengan Peran Transformational Leadership Yang Dimediasi Oleh Psychological Contract (Studi Pada Industri Bucini Leather Yogyakarta) Empirical Investigation Efforts to Improve Employee Performanc - Amalia Lisniawati (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2020)
The purpose of this study is effort to improve employee performance with the role of transformational leadership mediated by psychological contract. The subjects in this study were employees of the Bucini Leather industry especially in the production section with 110 people and 75 people taken as samples.The results of this study show that (1) Transformational leadership has a positive and significant effect on the psychological contract, (2) psychological contracts have a positive and significant effect on employee performance, (3) Transformational leadership has a positive and significant effect on employee performance, (4) Variable psychological contracts ) does not mediate the relationship between Transformational Leadership and employee performance (Y), with the results of the sobel test calculated <t-table (1.708 <1.9930)..